2015
DOI: 10.1051/matecconf/20152804003
|View full text |Cite
|
Sign up to set email alerts
|

Force/Torque Data Modeling for Contact Position Estimation in Peg-in-Hole Assembling Application

Abstract: Abstract. This paper presents an approach for estimating contact positions of peg-in-hole assembling application using data models created from Force/Torque sensor inputs. The assembling task is carried by an industrial robot where the F/T sensor is mounted between the robot and the gripper to measure six values of forces and torques during the contact between the peg and the hole. The search approach to estimate the current position of the contact point is implemented based on human like intuitive behavior by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…What is more, Sigitas et al investigated the high-speed assembly process with vibrations, and they found that the vibrations can be helpful for avoid jamming state, which is useful for finishing the assembly task smoothly (Kilikevicius and Baksys, 2011). Abdullah et al (2015a, 2015b) combined a vision sensor with a force sensor to help the robot successfully assemble. Furthermore, Son, 2001 presented a neural network control strategy for avoiding jamming during part insertion, which was based on measured force and moment data.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, Sigitas et al investigated the high-speed assembly process with vibrations, and they found that the vibrations can be helpful for avoid jamming state, which is useful for finishing the assembly task smoothly (Kilikevicius and Baksys, 2011). Abdullah et al (2015a, 2015b) combined a vision sensor with a force sensor to help the robot successfully assemble. Furthermore, Son, 2001 presented a neural network control strategy for avoiding jamming during part insertion, which was based on measured force and moment data.…”
Section: Introductionmentioning
confidence: 99%